A flexible, parallel, adaptive geometric multigrid method for FEM - Clevenger, Thomas Conrad; Heister, Timo; Kanschat, Guido; Kronbichler, Martin (ACM transactions on mathematical software, 2020)
We present the design and implementation details of a geometric multigrid method on adaptively refined meshes for massively parallel computations. The method uses local smoothing on the refined part of the mesh. Partitioning is achieved by using a space filling curve for the leaf mesh and distributing ancestors in the hierarchy based on the leaves. We present a model of the efficiency of mesh hierarchy distribution and compare its predictions to runtime measurements. The algorithm is implemented as part of the deal.II finite-element library and as such available to the public.